Study of relationship between optimism and resilience in the times of COVID-19 among university students - Dr. Aruna Maheshwari; Ms. Varda Jutta (International Journal of Indian Psychȯlogy, 2022)
The purpose of present research is to study the effect of COVID-19 Pandemic on the relationship between Optimism and Resilience among the university students. Optimism and Resilience of 100 university students (36 males and 64 females) were assessed by using optimism pessimism scale and a brief resilience scale. Digital survey method was adopted to reach out to the university students between 18-23 yrs. of age group and Pearson correlation coefficient method was used to establish the relationship between the variables. As a result, it was found that optimism and resilience share a positive relationship (0.507) not only otherwise but in the challenging times too. Findings revealed that to increase the resilience one has to increase the positive and optimistic thoughts. The research can add value to the detailed study on optimism and its relation with resilience and psychological well-being during unforeseen period. This study also gives further opportunity for a comparative study between the optimism and resilience among different age groups.